2018
DOI: 10.1097/mco.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

Metformin

Abstract: Several human and animal studies emphasized that metformin alters the gut microbiota composition by enhancing the growth of some bacteria, such as Akkermansia muciniphila, Escherichia spp. or Lactobacillus and by decreasing the levels of some other ones like Intestinibacter. In-vitro studies also demonstrated a direct action of metformin on the growth of A. muciniphila and Bifidobacterium adolescentis. Moreover, in the intestines, metformin does not only improve the glucose uptake, but it also promotes the sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…This is consistent with the hypothesis that changes in substrate availability in the lumen lead to bacterial abundance changes, as observed in our study. Our observation is supported by previous studies reporting that Metformin improved intestinal glucose sensing, as well as enhanced production of SCFA and gut peptides [41], even when the nutrient intake among members of PRE and T2D−M groups was similar. Currently, there is evidence suggesting that gut microbiota has an active role in the antidiabetic effects of pharmacological treatments [14]; so far, the most studied drug is metformin.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the hypothesis that changes in substrate availability in the lumen lead to bacterial abundance changes, as observed in our study. Our observation is supported by previous studies reporting that Metformin improved intestinal glucose sensing, as well as enhanced production of SCFA and gut peptides [41], even when the nutrient intake among members of PRE and T2D−M groups was similar. Currently, there is evidence suggesting that gut microbiota has an active role in the antidiabetic effects of pharmacological treatments [14]; so far, the most studied drug is metformin.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that metformin modulates the gut microbiota composition by increasing the growth of some bacteria, such as Akkermansia muciniphila , Escherichia spp. or Lactobacillus and by decreasing the levels of some other bacteria such as Intestinibacter [ 57 ]. However, metformin treatment has adverse effects such as diarrhea, nausea, heartburn and gas and it may negatively influence the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin also exerts anti-inflammatory effects [ 29 , 30 ]. It was recently reported that these effects might be related to the alteration of gut microbiota [ 31 ]. These results suggest that metformin can be used for the treatment of cancer.…”
Section: Immunomodulatory Effects Of Drugs Used For Treating Commomentioning
confidence: 99%